Systematic studies in the genus Melianthus L. (Melianthaceae) - Dlamini, Titus (Department of Biological Sciences, 2015)
The taxonomy and biology of Melianthus is reviewed. The taxonomic ranks of the two subspecies, M. dregeanus ssp. insignis and M. pectinatus ssp. gariepinus, are considered. A phenetic analysis indicates that M. insignis is similar to M. dregeanus but distinct enough to be recognised as a separate species. Though M. pectinatus ssp. gariepinus has not been investigated in detail, the implication of the resolved phylogeny on its status is discussed. The phylogeny of Melianthus and related taxa is reconstructed using cladistic analysis of morphological characters including vegetative morphology, pollen structure, seed-coat structure and the extremely diverse floral morphology. Bersama and Greyia, the probably sister species are used as outgroups for the analysis. The monophyly of MeIianthus is demonstrated, M. major is retrieved as the basal taxon for the study group and the rest of the species are scattered between two major clades. Species distributions are mapped and the pattern indicates that Melianthus has adapted to the Afromontane grasslands in the east of southern Africa as well as the semi-arid parts in the west. In terms of this distribution and the presumed phylogeny, the extent to which the situation in Melianthus supports existing ideas on the evolution of the southern African flora is explored. Ecological preferences for the species are described, then the extent to which they might have driven speciation in the genus is investigated. Evidence from floral ontogeny, indicating that the developmental pathways in Melianthus flowers vary quantitatively, hence the diversity, is also presented. Modifications of the basic Melianthus flower, which may have led to the complex structure in the genus, are considered and floral adaptations to pollinators are investigated. The role of pollinators in the evolution of floral diversity in Melianthus is also investigated. Finally, a key and full descriptions of all the species are provided.